Extraction without reserve: The case of Arizona's penal care regime - Strong, Justin D (Punishment & society, 2023)
Prison healthcare reform and litigation have emerged as critical sites of social and political struggle in early twenty-first century punishment. In the case of Arizona, privatization of its prison healthcare system maintained commitments to cheap and mean punishment in the wake of economic crisis, which led to an ongoing class-action lawsuit over prisoners’ rights violations. By conducting a case study of Arizona's prison healthcare crisis, this article mobilizes important interventions in the theoretical accounts of late mass incarceration and the penal state. Not only did Arizona's brand of penal austerity anticipate the scaling back of social services across the state, but effectively subjected prisoners to a perpetual deferment of care. Drawing upon this sociopolitical context, I elaborate a theory of penal extraction whereby care capacity is not only removed from the prison, but the prisoner's life becomes like an exhaustible resource.